Association between diet and physical activity and sedentary behaviours in 9-10-year-old British White children (2013)
Objectives To examine the association between diet and physical activity and sedentary behaviours in 9–10-year-old children. Study design A cross-sectional study using data from the SPEEDY (Sport, Physical activity and Eating behaviour: Environmental Determinants in Young People) study undertaken in Norfolk, UK. Methods Data from 4-day food diaries and 7 days of accelerometery were matched on concurrent days. Time spent in moderate-to-vigorous physical activity (MVPA), time spent in sedentary behaviour and various measures of dietary intake were collected. Covariates included age, sex, weight status, family socio-economic status, and energy intake reporting quality. Multivariable regression models, adjusted for clustering of children by school and stratified by sex, were fitted to examine the associations between dietary measures and physical activity and sedentary outcomes. Results In total, 1317 children (584 boys and 733 girls) provided concurrent data. Boys in the highest quartile of energy percentage from protein spent approximately 6 min [95% confidence interval (CI) 0–12] less in MVPA compared with boys in the lowest quartile. Those in the highest quartiles of fruit and vegetable intake and fruit juice intake had respective average activity counts per minute that were 56 above (95% CI 8–105) and 48 below (95% CI 2–95) those in the lowest quartiles, whilst those in the highest quartile of fizzy drink consumption spent approximately 7 min (95% CI 2–13) more in MVPA and approximately 14 min (95% CI 5–24 min) less in sedentary behaviour. Boys in the highest quartile of savoury snack consumption spent approximately 8 min (95% CI 2–13 min) more in MVPA per day, and approximately 12 min (95% CI 2–23) less in sedentary behaviour. No significant associations were apparent among girls. Conclusions Few associations were detected, and the directions of those that were apparent were mainly counterintuitive. The extent to which this reflects a true lack of association or is associated with the measurement methods used for diet and physical activity needs further investigation.